PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN GEOGRAFI KELAS X.7 SMA NEGERI 1 NAN SABARIS KABUPATEN PADANG PARIAMAN - Baiyar Mansur (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2016)
ABSTRACT This study aims to identify and understand the increased activity and student learning outcomes in the implementation of the learning model using a model cooperatif geography of NHT type. This research is Classroom Action Research (PTK). The subjects were X.7 Class SMAN 1 Padang Pariaman District Nan Sabaris the second semester of academic year 2013/2014 the number of students as many as 33 people consisting of 17 men and 16 women, where the selection is based on the research subject activities and student learning outcomes are still low. The results of this study indicate that: 1) Student learning activities with the learning model cooperatif NHT type the Geography classroom learning X.7 Nan Sabaris SMAN 1 Padang Pariaman District can be implemented according to plan, in which the activity of the students at the end of the cycle reaches a very high activity category with value of 88.79%. 2) The results of student learning in the classroom teaching Geography X.7 Nan Sabaris SMA 1 Padang Pariaman District with cooperatif NHT type can be improved with the achievement of mastery learning is able to provide the level of 87.5% and only 12.50% of students who are not able to provide completeness in learning Geography. This means that full implementation of each phase of a class action (PTK) may exceed the achievement of specified targets, namely 80%. 3) The student activity dibatu by the teacher directly collaborator in learning Geography with cooperatif NHT type can be considered excellent given. Activities students have been able to achieve the learning targets at each cycle III, so that students can achieve the learning outcomes exceeds a predetermined KKM.